INFLUÊNCIA DOS DEJETOS LÍQUIDOS DE SUÍNOS NA QUALIDADE DO SOLO EM ÁREAS AGRÍCOLAS COM DIFERENTES ANOS DE APLICAÇÃO - Mosele, Ana Caroline (2019)
Pig farming is one of the most important economic activities for the agricultural sector in the southern region of Brazil. Its development constitutes a factor of great importance for the economic growth of Brazil. Despite the profit and the technological advances applied in the production of pork, pig farming presents problems with the environment due to the waste produced by these animals. Among the alternatives for the final destination of swine manure, the use as fertilizer for the soil is one of the best options, besides being the most accepted by the farmers. The objective of this research was to identify possible changes in the physical and chemical quality of the soil after application of pig slurry in agricultural areas with different scales of application years. The research was carried out in a farm in the rural area of the municipality of Irati, Paraná – Brazil. For this research, we used four areas: A5 with 5 years of application of liquid slurry; A3 with three years of application, A1 with one year of application and AC - control area without application. Soil management was the same in all areas. our hypothesis is that the addition of liquid pig slurries improves the physical and chemical quality of the soil, and the longer the application time, the more significant are these improvements. The density, porosity and stability of soil aggregates (soil physical attributes) presented relevant differences after five years of application. The values related to chemical quality (pH and organic matter) did not indicate significant differences between the years of application of pig slurry. Therefore, we conclude that 5 years of application of pig slurry changes the soil physical conditions, but does not significantly alter the chemical conditions.